2022
DOI: 10.3390/biology11010058
|View full text |Cite
|
Sign up to set email alerts
|

Species-Specific Flash Patterns Track the Nocturnal Behavior of Sympatric Taiwanese Fireflies

Abstract: It is highly challenging to evaluate the species’ content and behavior changes in wild fireflies, especially for a sympatric population. Here, the flash interval (FI) and flash duration (FD) of flying males from three sympatric species (Abscondita cerata, Luciola kagiana, and Luciola curtithorax) were investigated for their potentials in assessing species composition and nocturnal behaviors during the A. cerata mating season. Both FI and FD were quantified from the continuous flashes of adult fireflies (lastin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(18 citation statements)
references
References 43 publications
0
18
0
Order By: Relevance
“…The specimens were collected as previously described in Goh, Lee & Wang (2022) . The material collected in this study was identified by LJ Wang on the species level through the use of available references ( Ballantyne et al, 2013 ; Chen, 2003 ; Jeng, Lai & Yang, 2003 ; Jeng, Yang & Lai, 2003 ; Jeng et al, 1998 ).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The specimens were collected as previously described in Goh, Lee & Wang (2022) . The material collected in this study was identified by LJ Wang on the species level through the use of available references ( Ballantyne et al, 2013 ; Chen, 2003 ; Jeng, Lai & Yang, 2003 ; Jeng, Yang & Lai, 2003 ; Jeng et al, 1998 ).…”
Section: Methodsmentioning
confidence: 99%
“…The material collected in this study was identified by LJ Wang on the species level through the use of available references ( Ballantyne et al, 2013 ; Chen, 2003 ; Jeng, Lai & Yang, 2003 ; Jeng, Yang & Lai, 2003 ; Jeng et al, 1998 ). Five morphological characteristics of the specimens (body length, pronotum length, pronotum width, front wing length, and front wing width) were measured (see Table S3 ) using a dissecting microscope and photographed with a digital video camera as previously described in Goh, Lee & Wang (2022) . During the survey, the specimens were chilled on ice.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…can be of immense value in identifying firefly populations on the decline. These programs should be continued, expanded, and where possible unified into a single standardized platform that supports species identification (by trained observers or machine-learning algorithms, e.g., Goh et al, 2022). The responses of fireflies to ALAN are highly species-specific, and measures of general firefly activity without accompanying species information can be compromised by changes in species composition.…”
Section: Conservation Recommendationsmentioning
confidence: 99%